2020
DOI: 10.1088/2051-672x/ababf5
|View full text |Cite
|
Sign up to set email alerts
|

Laser surface texturing of Wankel engine apex seals

Abstract: Wankel rotary engines are used as power units in contemporary machines such as unmanned aerial vehicles and automobile range extenders due to their high-power density. A challenge of the engine architecture is the maintenance of an effective seal around each chamber while simultaneously minimising parasitic frictional losses. This paper investigates, experimentally, the suitability of laser surface texturing to reduce frictional losses at the apex seal-housing interfaces of Wankel engines. To inform the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The ability to account for transient loads has enabled the calculation of dynamic coefficients [130]. For sealing applications, analytical modelling has been used to design apex seals used in Wankel engines [159]. A numerical model showed significant improvements in the static and dynamic performance of a foil air journal bearings for textures consisting of either dimples or grooves when compared with a conventional plain foil [165].…”
Section: Surface Texturingmentioning
confidence: 99%
“…The ability to account for transient loads has enabled the calculation of dynamic coefficients [130]. For sealing applications, analytical modelling has been used to design apex seals used in Wankel engines [159]. A numerical model showed significant improvements in the static and dynamic performance of a foil air journal bearings for textures consisting of either dimples or grooves when compared with a conventional plain foil [165].…”
Section: Surface Texturingmentioning
confidence: 99%
“…Laser-based surface texturing is an alternate and economical approach to achieve corrosion resistance on cold rolled materials. 31,32 Laser irradiation of materials induces chemical modifications on the surface to enhance corrosion resistance. 33,34 Laser-based texturing has gained attraction for surface modification due to exceptional control on the target sites and the ease of operation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a textured circumferential gas seal, Kligerman et al [26] found significant improvement in the hydrodynamic effect, which prevents rubbing and wear between the shaft and seal ring. Laser surface texturing in the Wankel rotary can reduce friction power loss by about 30% [27]. In piston ring/cylinder liner contact, optimally designed textures enhanced the lubrication condition both near the top dead center by increasing minimum clearance and at mid-stroke by decreasing the minimum clearance [28].…”
Section: Introductionmentioning
confidence: 99%